Development of Microteaching Learning Device Prototypes based on Hybrid Learning, Faculty of Teacher Training and Education, University of West Sulawesi - Hajati, Kartika; Musdar, Musdar; Ariandi, Ariandi (Kasuari: Physics Education Journal (KPEJ), 2023)
The aim of this study was to develop prototypes of microteaching learning devices based on hybrid learning at the Teaching and Education Faculty of the University of West Sulawesi that meet content validity. The type of research used is Research and Development (R&D) with the development design of the Four-D Model. The research subjects were expert validators, and prospective users, namely FKIP University of West Sulawesi lecturers in charge of the microteaching course and students of the Teaching and Education Faculty of the University of West Sulawesi who would program the Microteaching course. The content validation results from 2 expert validators on the Semester Learning Plan were 93.75%. The results of the handout and video validation assessment were 92.44%. The results of the validation of the observation sheet validation were 93.05%. Meanwhile, student assessment on the handout accompanied by video was 79.62%. Therefore, based on the results obtained the development of this learning prototype fulfills content validity or can be said to be valid